2015
DOI: 10.1002/14651858.cd011006.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for the treatment of depression in people with cancer

Abstract: Despite the impact of depression on people with cancer, available studies were very few and of low quality. This review found very low quality evidence for the effects of these drugs compared with placebo. On the basis of these results clear implications for practice cannot be made. The use of antidepressants in people with cancer should be considered on an individual basis and, considering the lack of head-to-head data, the choice of which agent should be prescribed may be based on the data on antidepressant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 111 publications
4
83
0
6
Order By: Relevance
“…The large discrepancy between rates of documented depressive symptoms and of use of antidepressant medications in our sample aligns with prior literature, which has demonstrated that most adults who screen positive for depression are not receiving treatment for depression, and conversely, most who receive depression treatment do not necessarily screen positive for depressive symptoms [57]. Difficulties assessing depressive symptoms among patients with cancer could also contribute to this discrepancy, as oncology clinicians may struggle to distinguish between pathological mood symptoms and normal reactions to severe illness [24,28,29,58]. Despite these challenges, our study suggests that active depressive symptoms documented by outpatient clinicians can help identify a high-risk group of patients with advanced cancer.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The large discrepancy between rates of documented depressive symptoms and of use of antidepressant medications in our sample aligns with prior literature, which has demonstrated that most adults who screen positive for depression are not receiving treatment for depression, and conversely, most who receive depression treatment do not necessarily screen positive for depressive symptoms [57]. Difficulties assessing depressive symptoms among patients with cancer could also contribute to this discrepancy, as oncology clinicians may struggle to distinguish between pathological mood symptoms and normal reactions to severe illness [24,28,29,58]. Despite these challenges, our study suggests that active depressive symptoms documented by outpatient clinicians can help identify a high-risk group of patients with advanced cancer.…”
Section: Discussionsupporting
confidence: 81%
“…However, although therapies are available to help address depressive symptoms in patients with cancer, prior studies have not investigated the potential impact of such therapies on the use of health care services. Clinicians frequently use antidepressant medications to treat depressive symptoms among patients with cancer, and studies have shown that the use of antidepressant medications can help decrease psychological distress in this population [21,22,28,29]. In addition, research has demonstrated that proactive use of antidepressant medications for patients with cancer may help prevent the development of depressive symptoms [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the effective management of depression is essential to improving both quality of life and survivorship in cancer patients. Although late-stage cancer patients are far more likely than the general population to be prescribed an antidepressant3, a recent meta-analysis did not find a significant difference in efficacy between antidepressants and placebo in treating cancer patients with depression symptoms4. This study, in addition to previous systematic reviews, emphasizes the scarcity of high quality evidence for the effect of antidepressants in cancer-induced depression (CID)4567.…”
mentioning
confidence: 66%
“…Prevalence rates of major depression among cancer patients are four times higher than the general population (Bortolato et al, 2017;Ostuzzi, Matcham, Dauchy, Barbui, & Hotopf, 2015) and up to a quarter of oncologic patients have clinically significant depressive and anxiety symptoms (Mitchell et al, 2011;Pirl, 2004). These rates increase in patients with poorer prognosis (Benton, Staab, & Evans, 2007) and in end stages of the disease (Lo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To-date, only scarce and methodologically limited reports yielding contradictory data are available on this issue (Ostuzzi et al, 2015;Ostuzzi, Matcham, Dauchy, Barbui, & Hotopf, 2018).…”
Section: Introductionmentioning
confidence: 99%